1984
DOI: 10.21273/jashs.109.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Root-zone Heating on Elemental Composition of Calceolaria

Abstract: Root-zone heating increased the tissue concentration and total uptake of N, P, K, Ca, Mg, S, Cl, Fe, MnZn, and Cu; decreased the tissue concentration but not total uptake of Na and Zn, and had no effect on the tissue concentration of B. The element with the greatest increase in concentration in the shoot was water-soluble NO3-N. The ratio of cations to anions did not change significantly with changes in root-zone temperature. The concentration and balance of cations did not change significantly with changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Interestingly, under low-temperature stress, although ABA was able to promote iron accumulation, iron accumulation in leaves did not decrease substantially after ABA synthesis was inhibited ( Figure 7 ). To initially investigate the regulatory principles, we measured the expression of SlZIP1 and SlZIP3 , key genes involved in iron transport, after external application of ALA and ABA at low temperature and found that they were significantly up-regulated ( Figure S2 ) [ 38 ]. Therefore, we speculated that it is because inhibition of ABA synthesis leads to an increase in ALA content, which can also promote the expression of iron transporter-related genes and iron accumulation, thus counteracting the negative effects of the ABA synthesis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, under low-temperature stress, although ABA was able to promote iron accumulation, iron accumulation in leaves did not decrease substantially after ABA synthesis was inhibited ( Figure 7 ). To initially investigate the regulatory principles, we measured the expression of SlZIP1 and SlZIP3 , key genes involved in iron transport, after external application of ALA and ABA at low temperature and found that they were significantly up-regulated ( Figure S2 ) [ 38 ]. Therefore, we speculated that it is because inhibition of ABA synthesis leads to an increase in ALA content, which can also promote the expression of iron transporter-related genes and iron accumulation, thus counteracting the negative effects of the ABA synthesis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Energy conservation practices should reduce energy consumption per unit of fresh or dry weight while maintaining or increasing plant quality. Reduced air temperatures for part of the night (SN heating), and soil warming (RZ heating) can reduce energy consumption (2,4,7,9,14,16). Studies have examined whole-plant growth responses to RZ temperatures (3,8,10), but few have considered the seedling growth period separately.…”
mentioning
confidence: 99%